The Effect Of Destination Image And Servicescape, With Patient Experience As An Intervening Variable, On Revisit Intention At The Outpatient Unit Of RSUD Cempaka Putih - Rotua Simanjuntak, Imelda; Hilmy, Reza; Wahid, Kemala Rita (Syntax Literate, 2026)
Background: Hospital services today are required not only to provide quality medical services, but also to create a positive patient experience in order to increase trust and intention for repeat visits. Cempaka Putih Hospital faces challenges related to the image of the destination and the comfort of the physical environment of the service, especially due to market activities around the hospital, traffic density, and inconsistencies in communication between health workers. The purpose of this study aims to analyze the influence of destination image and servicescape on revisit intention with patient experience as an intervening variable in the Outpatient Unit of Cempaka Putih Hospital. This research method uses a quantitative approach with a coss-sectional design, involving 200 patients who visited  2 times in the outpatient unit of Cempaka Putih Hospital as respondents who were selected through saturated sampling techniques, Data were collected using questionnaires and analyzed with Structural Equation Model (SEM) with Amos 25. The results of this study show that destination image, servicescape and patient experience have a significant effect on revisit intention. In addition, patient experience has been proven to be an intervening variable that mediates the relationship between the two independent variables and revisit intention. The managerial implication of this study is that there is a need to increase the intention of revisiting patients not only depending on the quality of medical services, but also on strengthening the hospital's destination image, improving the physical environment, and improving the quality of communication and patient experience. This research emphasizes the importance of holistic strategies that include cross-sector collaboration, human resource capacity building, and continuous monitoring of patient experience to strengthen hospital destination image and drive patient loyalty.